Implementasi Model Edukasi Interaktif Sebagai Sarana Pengembangan Karakter Anak di LKSA Sabilul Muhtadien - Cindya Alfi; Afifatul Izzatil Husna; Deni Tri Lutfiana; Elsa Nadya Ulandari; Fatqul Anang Ma’ruf; Julia Masrifatin; Li’ana Turosidah; Muhammad Amiqul Ilmi; Muhammad Tegar Amru; Putri Ayu Maharani; Putri Nanda Sholikah; Slamet Supriadi; Tsaniatul Muyassaroh; Vitika Kurniawati; Widya Putri Mailani (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Children in orphanages often face unique challenges in character formation due to limited educational stimulation and diverse social interactions, despite their basic needs being met. The interactive education model applied in the "Devotion in Action, Love in Education: Weaving Character with the Nation's Children" project focuses on a participatory approach through activities such as Story Telling, "Tree of Goodness," Ball Relay, and Water Balloon Volleyball. This research aims to analyze the effectiveness of implementing an interactive education model in the character development of children at Sabilul Muhtadien Orphanage in Plosokerep, Sananwetan District, Blitar City. The research method employed is a case study with a qualitative approach, reinforced by participatory observation and informal interviews with caregivers and children from the orphanage. The results indicate high enthusiasm from the children and positive responses from caregivers, signifying the program's success in instilling character values such as critical thinking, mutual cooperation, creativity, independence, and solidarity. The implications of this research highlight the importance of adopting dynamic and activity-based education models in efforts to shape children's character in orphanages, focusing not only on knowledge transfer but also on direct experience and holistic potential development. holistik.